2008
DOI: 10.1007/s11270-008-9818-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphate on the Arsenic Uptake by Wheat (Triticum durum L.) Irrigated with Arsenic Solutions at Three Different Concentrations

Abstract: In this study we have investigated the uptake and distribution of arsenic (As) and phosphate (P i ) in roots, shoots, and grain of wheat grown in an uncontaminated soil irrigated with solutions containing As at three different concentrations (0.5, 1 and 2 mg l −1 ) and in the presence or in the absence of P fertilization. Arsenic in irrigation water reduced plants growth and decreased grain yield. When P i was not added (P−), plants were more greatly impacted compared to the plus P i (P+) treatments. The diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
56
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 42 publications
18
56
2
Order By: Relevance
“…At present, soybeans are grown in prime soils and also in marginal lands, where the occurrence of some As-contaminated soils has been documented for many years [16]. Bustingorri et al [13] found a negative correlation between soybean yields and soil As concentration, in agreement with similar studies in rice, wheat, and barley [7,17].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…At present, soybeans are grown in prime soils and also in marginal lands, where the occurrence of some As-contaminated soils has been documented for many years [16]. Bustingorri et al [13] found a negative correlation between soybean yields and soil As concentration, in agreement with similar studies in rice, wheat, and barley [7,17].…”
Section: Introductionsupporting
confidence: 60%
“…Aerial biomass was less affected by As than roots in non-inoculated plants as described for rice, wheat [5,7,17], and soybeans [14]. Resembling the findings of other authors [26], inoculated plants were less affected by As.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Arsenate is known to interfere in phosphate (P) uptake by plant cells since P transporters had high affinity to As, therefore competing with P anions (Finnegan & Chen 2012). Competition between As and P physiologically results in blocking the electron transport chain at the level of cell membranes, and therefore ATP synthesis is significantly inhibited (Pigna et al 2009). This leads to the disruption of energy flows in cells and finally represses the growth and development of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phosphorus (P) can compete with As for adsorption sites in soils and correspondingly increase the mobility and availability of As because of their similar chemical behaviours (Smith et al 2002). Studies have been carried out to explore the interaction between As and P adsorption on clay minerals, Fe/Al oxides/hydroxides, or intact soils (Liu et al 2001, Violante and Pigna 2002, Pigna et al 2009). However, the adverse effects of P application on As adsorption might vary in different soils.…”
mentioning
confidence: 99%